2013
DOI: 10.1002/cbin.10036
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term muscle‐derived cell culture: multipotency and susceptibility to cell death stimuli

Abstract: Improvement in the yield of adult organism stem cells, and the ability to manage their differentiation and survival potential are the major goals in their application in regenerative medicine and in the adult stem cell research. We have demonstrated that adult rabbit muscle-derived cell lines with an unlimited proliferative potential in vitro can differentiate into myogenic, osteogenic, adipogenic and neurogenic lineages. Studies of cell survival in vitro showed that differentiated cells, except neurogenic one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…It is known that muscle-derived stem cells can be cultured in vitro as permanent lines and under certain conditions they give rise to different kinds of progeny cells, making them a suitable model for pharmacological and toxicological studies. We have shown that adult rabbit muscle-derived Myo cell lines with an unlimited proliferative potential in vitro can differentiate into myogenic, osteogenic, adipogenic and neurogenic lineages (Kalvelyte et al, 2013). Our data prove that proliferating and differentiated cells have different susceptibility to cytotoxic agents, e.g.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…It is known that muscle-derived stem cells can be cultured in vitro as permanent lines and under certain conditions they give rise to different kinds of progeny cells, making them a suitable model for pharmacological and toxicological studies. We have shown that adult rabbit muscle-derived Myo cell lines with an unlimited proliferative potential in vitro can differentiate into myogenic, osteogenic, adipogenic and neurogenic lineages (Kalvelyte et al, 2013). Our data prove that proliferating and differentiated cells have different susceptibility to cytotoxic agents, e.g.…”
Section: Introductionsupporting
confidence: 59%
“…Our data prove that proliferating and differentiated cells have different susceptibility to cytotoxic agents, e.g. Myo cells differentiated into myogenic, osteogenic and adipogenic lineages appeared to be more resistant to apoptosis inducers compared to proliferating cells (Kalvelyte et al, 2013).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, it is also worth investigating mechanisms by which normal cells acquire resistance to death induction and stress conditions during differentiation. For example, mouse, rabbit and human differentiating muscle cells display differentiation-induced resistance to genotoxic agents, as well as diminished susceptibility to apoptosis [100104]. Conversely, some investigators suggested that undifferentiated cells are more resistant to oxidative stress, probably because of a higher level of intracellular redox system, which is characteristic of stem cells [105, 106].…”
Section: Transplantable Cell Death/survival Signalingmentioning
confidence: 99%
“…The major mediator of this pathway is the AKT kinase which is implicated in stem cell and myocyte survival, myogenesis, in part by promoting the expression of various molecules including the myogenin gene [109112]. Moreover, both AKT1 and AKT2 proteins and kinase activities are upregulated during myogenic differentiation and are tightly associated with apoptosis-resistance [104, 110, 112, 113]. In particular, AKT signaling in the infarcted heart can block apoptosis, decrease infarct size, and increase left ventricular wall thickness compared to pre-infarction condition [114, 115].…”
Section: Transplantable Cell Death/survival Signalingmentioning
confidence: 99%